The Influence of Different Land Transportation Time from Banjarnegara to Semarang on Body Condition Response of Local Male Sheep - herwinda, fauzia alma; Purnomoadi, Agung; Adiwinarti, R.R. Retno; Riyanto, Edy; Restitrisnani, Vita; Purbowati, Endang (Jurnal Ilmu Ternak Universitas Padjadjaran, 2023)
This study aims to determine the body conditions and body weight loss of male local sheep after transportation from Banjarnegara to Semarang at different times. This study used 22 local rams aged 10 months weighing 17.14 + 1.68 kg (CV= 9.8%). This research used a Completely Randomized Design with two treatments and 11 replications. The treatments were different transportation times consisting of 4 hours (T1) and 6 hours (T2). The parameters used in this study were pulse rate, respiratory rate, and rectal temperature in Banjarnegara (before transportation), Temanggung (during rest), and Semarang (after transportation), as well as body weight loss from male local sheep. The data were analyzed by using a t-test. The results showed that before transportation, the pulse and respiratory rate of T2 rams were higher (P<0.05) than those of T1, however, their body temperatures were relatively the same as the average (35.86 oC). During rest, the pulse rate, respiratory rate, and body temperature of T1 and T2 were relatively the same with an average of 97 times/minute, 57 times/minute and 35.85 oC, respectively. After transportation, the pulse rate of T1 was higher (P<0.05) compared to T2, while the respiratory rate and body temperature of T1 were lower (P<0.05) than those of T2. The body weight of the sheep before and after transportation between T1 and T2 was not significantly different (P>0.05) with an average of 18.33 kg before transportation and  16.80 kg after transportation. The body weight loss of T1 and T2 was about 1.53 kg, and was not significantly different (P>0.05). It can be concluded that different transportation times (4 hours and 6 hours) affected local rams’ physiological conditions with similar body weight loss.Key words : sheep, transportation, physiological conditions, and body weight loss.